1993
DOI: 10.1001/jama.269.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and risk of Graves' disease

Abstract: Smoking is associated with Graves' disease, and it especially increases the risk for the development of more severe ophthalmopathy. Thus, smoking appears to be one of the multiple factors inducing Graves' disease in genetically predisposed individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
105
5
10

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(126 citation statements)
references
References 0 publications
4
105
5
10
Order By: Relevance
“…We believe that the difference in gender ratio may be attributed to the high prevalence of male smokers (68.4%) in our study. The mean age of our patients was 40.7 years at presentation; lower than previous studies8 9 which had reported 49.2 and 46.4 years respectively. This may be attributed to the existence of a multidisciplinary Thyroid Eye Clinic at our institution, where close cooperation between the ophthalmologist and endocrinologist ensures early diagnosis and treatment of patients with TED.…”
Section: Discussioncontrasting
confidence: 67%
“…We believe that the difference in gender ratio may be attributed to the high prevalence of male smokers (68.4%) in our study. The mean age of our patients was 40.7 years at presentation; lower than previous studies8 9 which had reported 49.2 and 46.4 years respectively. This may be attributed to the existence of a multidisciplinary Thyroid Eye Clinic at our institution, where close cooperation between the ophthalmologist and endocrinologist ensures early diagnosis and treatment of patients with TED.…”
Section: Discussioncontrasting
confidence: 67%
“…This interpretation could be in line with recent observations that smoking protects against the development of TPO-Ab (17) and also against the development of hypothyroidism (18,19). We could not ascertain the well-known risk of smoking for developing Graves' hyperthyroidism, most likely to the small sample size (20).…”
Section: Discussionsupporting
confidence: 65%
“…It has been reported that in areas with sufficient iodine intake, hypothyroidism is more common than in iodine-deficient regions (31), whereas the overall prevalence of thyrotoxicosis is greater in iodine-deficient areas (32). Smoking is a risk factor for Graves' disease (20). On the other hand, smoking decreases the risk on hypothyroidism (18,19) and has a protective effect on the development of TPO-Ab and Tg-Ab (17).…”
Section: Discussionmentioning
confidence: 99%
“…Smokers develop severe GO and they respond less to steroid treatment or radiotherapy than non-smokers (24,25). Cigarette smoking was the most striking risk factor detected in our active GO cases.…”
Section: Discussionmentioning
confidence: 72%